Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Use the formula [tex]\(A = \frac{1}{2} b h\)[/tex] to solve for [tex]\(b\)[/tex].

a) When [tex]\(A = 390\)[/tex] and [tex]\(h = 26\)[/tex].

b) In general (just the formula, [tex]\(b = ?\)[/tex]).


Sagot :

Sure, let's work through the problem step-by-step.

### Part (a) - Solving for [tex]\( b \)[/tex] when [tex]\( A = 390 \)[/tex] and [tex]\( h = 26 \)[/tex]:

We start with the formula for the area of a triangle:
[tex]\[ A = \frac{1}{2} b h \][/tex]

Given:
- [tex]\( A = 390 \)[/tex]
- [tex]\( h = 26 \)[/tex]

We need to solve for the base [tex]\( b \)[/tex].

First, substitute the given values of [tex]\( A \)[/tex] and [tex]\( h \)[/tex] into the formula:
[tex]\[ 390 = \frac{1}{2} b \cdot 26 \][/tex]

Next, isolate [tex]\( b \)[/tex] by performing the following steps:

1. Multiply both sides of the equation by 2 to eliminate the fraction:
[tex]\[ 2 \cdot 390 = b \cdot 26 \][/tex]
[tex]\[ 780 = b \cdot 26 \][/tex]

2. Divide both sides by 26 to solve for [tex]\( b \)[/tex]:
[tex]\[ b = \frac{780}{26} \][/tex]
[tex]\[ b = 30 \][/tex]

So, when [tex]\( A = 390 \)[/tex] and [tex]\( h = 26 \)[/tex], the base [tex]\( b \)[/tex] is [tex]\( 30 \)[/tex].

### Part (b) - Solving for [tex]\( b \)[/tex] in general:

To find the general formula for [tex]\( b \)[/tex], start from the area formula:
[tex]\[ A = \frac{1}{2} b h \][/tex]

We need to solve for [tex]\( b \)[/tex]. Rearrange the equation to isolate [tex]\( b \)[/tex]:
[tex]\[ \frac{1}{2} b h = A \][/tex]

First, multiply both sides by 2 to get rid of the fraction:
[tex]\[ b h = 2A \][/tex]

Then, divide both sides by [tex]\( h \)[/tex] to solve for [tex]\( b \)[/tex]:
[tex]\[ b = \frac{2A}{h} \][/tex]

This gives us the general formula for [tex]\( b \)[/tex] in terms of [tex]\( A \)[/tex] and [tex]\( h \)[/tex]:
[tex]\[ b = \frac{2A}{h} \][/tex]

Therefore, in general, the base [tex]\( b \)[/tex] can be calculated using the formula:
[tex]\[ b = \frac{2A}{h} \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.